Lipa City...Emerging City for All Seasons??? - Janet S. Cuenca; Ma. Libertad Dometita (Philippine Institute for Development Studies (PIDS), 2004)
The paper focuses on the socioeconomic development experience of Lipa in its journey to being an emerging city. Specifically, it presents the urbanization process in the city particularly the demographic and socioeconomic process with emphasis on the changing economic structure as well as the living condition of the populace. In addition, it investigates whether booming economic activities are attracting migrants and creating revenue-raising opportunities, which in turn will finance increasing demand for basic services. Lastly, the study attempts to identify the issues and challenges that come along with urbanization as well as the citys potentials for further economic development. These factors will determine whether Lipa City remains a promising city or transforms into a highly urbanized one.
Keywords: 330; urbanization; local governance; Lipa City; emerging city; Urbanisierung; Urbanistik; Kommunalverwaltung; Philippinen